Identifikasi Pola Makan Pada Pasien Lanjut Usia Dengan Hipertensi Di Wilayah Kerja Puskesmas Pare Kabupaten Kediri - Frenky Arif Budiman; Tutut Pujianto; Lona Rosinta (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract Hypertension is a circulatory system disorder that increases the increase in blood pressure above normal so that it has a risk of heart disease, stroke, and kidney failure. In hypertension, blood pressure increases due to blood pumping through blood vessels with excess force. Hypertension can be triggered by the consumption of inappropriate foods such as foods that contain lots of sugar, high salt, excessive fat such as thick coconut milk, oil, vegetables and fruits that contain gas, and drinks consumed every day with coffee. to identify an overview of the diet in advanced hypertension sufferers in Puskesmas Pare. This study used a cross sectional research design. With a sample of 15 patients. The results of the research on dietary patterns in patients greatly affect hypertension. It is proven that the majority of hypertension sufferers are in the 60-70 years age group. Meanwhile, the total intake of energy, carbohydrates, protein and fat is generally not in accordance with the recommendations for hypertension sufferers, namely> 60%. This is because the amount of energy, carbohydrate, protein, and fat intake is generally more which is not in accordance with the recommendations for people with hypertension. Based on the results of the research, it is recommended for Puskesmas Pare to carry out nutritional counseling or associations for hypertension sufferers to talk about all vitamins or nutrients in carrying out a diet or dietary regulation and provide recommendations to avoid and limit food such as consuming salty, sweet, and fatty so as not to cause complications. Keyword : Dietary habit, Hypertension, Elderly, Nutrition